2016
DOI: 10.1038/ni.3390
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase PP2A is requisite for the function of regulatory T cells

Abstract: Immune homeostasis depends on the proper function of regulatory T (Treg) cells. Compromised Treg cell suppressive activity leads to autoimmune disease, graft rejection and promotes anti-tumor immunity. Here we report the previously unrecognized requirement of the serine/threonine phosphatase Protein Phosphatase 2A (PP2A) for the function of Treg cells. Treg cells exhibited high PP2A activity and Treg cell-specific ablation of the PP2A complex resulted in a severe, multi-organ, lymphoproliferative autoimmune di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
218
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(225 citation statements)
references
References 56 publications
6
218
1
Order By: Relevance
“…Indeed, PP2A signaling was recently shown to be crucial for Treg function. The catalytic activity of PP2A in Tregs from mice was reported to be increased at levels significantly higher than in conventional Tconv cells [58]. In this study, mice deficient in PP2Ac Tregs developed spontaneously severe, progressive, multi-organ autoimmunity characterized by wasting, dermatitis, scaly tails and ears, eyelid crusting and in some occasions overt skin rash and ulcerations.…”
Section: Known Molecular Requirements For Treg Sustenance and Functionmentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, PP2A signaling was recently shown to be crucial for Treg function. The catalytic activity of PP2A in Tregs from mice was reported to be increased at levels significantly higher than in conventional Tconv cells [58]. In this study, mice deficient in PP2Ac Tregs developed spontaneously severe, progressive, multi-organ autoimmunity characterized by wasting, dermatitis, scaly tails and ears, eyelid crusting and in some occasions overt skin rash and ulcerations.…”
Section: Known Molecular Requirements For Treg Sustenance and Functionmentioning
confidence: 61%
“…Novel Treg-specific mechanisms relying on environmental and cytosolic cues to restrain mTORC1 have recently been described, and one example is protein phosphatase 2A (PP2A) [58]. Indeed, PP2A signaling was recently shown to be crucial for Treg function.…”
Section: Known Molecular Requirements For Treg Sustenance and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has demonstrated that PP2A inhibition also re-established the metabolic profile of Treg cells in PP2A flox mice [37]. These authors showed that the transgenic knockdown of PP2A resulted in augmented glycolytic activity and mitochondrial respiratory capacity in the PP2A flox Tregs.…”
Section: Discussionmentioning
confidence: 88%
“…[10][11][12][13][14][15] The recent observation, that CRP formation is essential in controlling the metabolic activity of regulatory T cells demonstrates that ceramides play also an essential role in regulating immune functions and inflammation. [16,17] However, despite these important roles the molecular organization of ceramides in the plasma membrane remains elusive. Hitherto, CRPs have been studied extensively in artificial membranes by biochemical and biophysical approaches [3,4,[18][19][20] and in fixed cells by immunocytochemistry.…”
Section: Graphical Abstractmentioning
confidence: 99%